ANALYSIS OF TOURISM COMPETITIVENESS IN THE CITY OF PARIAMAN USING DEVIDE AND CONQUER METHOD - Vicky Ariandi; Muhammad Afdhal; Hezy Kurnia (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
The department is one of the strategic departments to increase local income. Income from Tourism activities contribute to employment and promote employment in these fields Sub-industry of tourism. In this study, the subjects of tourism are untouchables The Regency is one of the areas with high-value tourism potential. In this study, the competitiveness of the tourism industry can be measured Use four indicators to measure competitiveness World Tourism Organization (WTO), namely Human Tourism Index (HTI), Infrastructure Development Index (IDI), Environmental Index (EI), Open Index (OI)). Secondary school data. The analytical method used in this study is tourism competitiveness index. Analysis shows that the 8th tourism industry competitiveness Indicator variable IDI (Infrastructure Development Index) environmental indicators (EI) indicates that this value is highly competitive, while other indicators have .low Competitiveness.